2020
DOI: 10.5624/isd.2020.50.3.217
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional evaluation of the mandibular symphyseal region in block graft harvesting for dental implants using cone-beam computed tomography

Abstract: Purpose: The purpose of this study was to analyze the quantity and quality of the mandibular anterior alveolar bone in terms of alveolar width, density, and total alveolar height (TAH) based on dental status, gender, and age. Additionally, this study aimed to quantitatively evaluate the available alveolar height for graft harvesting (AHGH) and examine its variability based on the aforementioned factors. Materials and Methods: This retrospective cone-beam computed tomographic study included a total of 100 subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Studies on the relationship between alveolar bone width and gender have reached different results. Some reported that gender had no effect, while others showed that the width of the alveolar bone in the edentulous regions in men was less than the symmetrical toothed side [20,21]. This study, on the other hand, found that the alveolar bone width in edentulous areas did not differ according to gender, and the bone width in incisor, premolar, and molar edentulous spaces was less than the toothed side.…”
Section: Discussioncontrasting
confidence: 51%
“…Studies on the relationship between alveolar bone width and gender have reached different results. Some reported that gender had no effect, while others showed that the width of the alveolar bone in the edentulous regions in men was less than the symmetrical toothed side [20,21]. This study, on the other hand, found that the alveolar bone width in edentulous areas did not differ according to gender, and the bone width in incisor, premolar, and molar edentulous spaces was less than the toothed side.…”
Section: Discussioncontrasting
confidence: 51%
“…Recommending a safety zone for bone harvesting was not the purpose of this study; however, according to the results of the current study and those of Gandhi V et al, who suggested conservative safe margins of 5mm away from vital structures and inferior cortex of the mandible for bone harvesting [ 11 ], bone length and height of 38 and 10 mm, respectively, could be considered for safe bone harvesting. Attention should be paid to the incisive canal in this safe zone to prevent injury to the mandibular incisive nerve and the associated vasculature in the process of bone harvesting.…”
Section: Discussionmentioning
confidence: 86%
“…According to the results of a previous study [ 11 , 12 ], the sample size was calculated to be 78 CBCT scans, using the following formula (α = 0.05, β = 0.2, d = 0.65, =4) …”
Section: Methodsmentioning
confidence: 99%